The effects of Ca14Mg2(SiO4)8:Eu2+ phosphor on white light emission quality of LED-phosphor packages - Thanh Tung, Ha; An Nguyen Thi, Dieu; Doan Quoc Anh, Nguyen (Bulletin of Electrical Engineering and Informatics, 2023)
Ca14Mg2(SiO4)8: Eu2+ (CMS:Eu2+) green phosphor is used for creating the white-light emitting diode (W-LED) packages with conversion phosphor materials. The phosphor shows the broadband green emission that peaks at 505 nm in the blue wavelength. The phosphor introduces the improvement in the blue and green emission spectra, which helps to heighten the luminous flux. Moreover, that the concentration of CMS:Eu2+ increases, the scattering events are enhanced to benefits the color blending for lower color variations or better color uniformity. The color renditions reduce with the rising green-phosphor concentration. The green-light amount becomes surplus and redundant for balancing color elements of white light emission. Thus, it should adjust and keep the concentration of CMS:Eu2+ in the range of ~2–8 wt%, to get the average number of color rendering index (CRI) (73–75), and color quality scale (CQS) (60–64). The CMS: Eu2+, hence, is suitable for white light realization, and the W-LED aiming at high-luminescence white light emission with improved color uniformity, and average rendering performances.